L’illusione del Super-Io. Riflessioni su Freud e Kelsen - Lijoi, Federico (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
In this essay I propose to analyse Kelsen’s reading of Freud’s Massenpsychologie by showing how the Austrian jurist used Freud’s essay to highlight their shared struggle against the application of the theological method in the social sciences. The result of this analysis, beyond noting some punctual divergences between the two authors, is that both proposed the idea that the authoritarian state and its religious connotation should be replaced by a scientific form of government, i.e. one free from the illusion that responsibility for our life in common can be replaced by a knowledge that guarantees its subsistence once and for all.